Severity and Endurance in Eating Disorders: An Exploration of a Clinical Sample From Chile - Dapelo, Marcela M.; Gil, Aurora A.; Lacalle, Lucas; Vogel, Melina (Frontiers in Psychiatry, 2020)
Introduction: In one in five patients with eating disorders (EDs) may take a lasting course. It has been proposed that this enduring group exhibits increased severity, such as low treatment response, severe symptomatology, and poor quality of life. However, there is no consensus defining this group. Moreover, most of the literature comes from high-income societies and may not apply to developing countries. Aims: This study aims to evaluate the association between endurance (length of ED) and severity (previous treatments, hospitalizations, complications, symptomatology and clinical impairment) in individuals with EDs from Chile. In addition, it aimed to explore the association between endurance and delays seeking specialized treatment. Methods: Forty-one women with EDs completed a demographic survey, EDE-Q, and CIA questionnaires. Also, BMI, length of ED, and complications were retrieved from medical records. Results: There was no significant association between length of ED and measures of severity. There was a significant association between length of ED and delays seeking specialized treatment (rs=0.72;p<0.01). Regression indicated that for each month in delay visiting a specialized ED treatment team, the ED duration increased by 0.87 months (F(1,38)=75.93; p<0.01; R2= 0.66). Discussion: The findings suggest that in countries where specialized treatment access is not widespread, defining SEED solely by the length of illness may not be clinically significant, and other criteria (e.g., timely access to evidence-based treatments) should be incorporated.